Sugar Binding in Lactose Permease: Anomeric State of a Disaccharide Influences Binding Structure - Klauda, Jeffery B. (2007)
Lactose permease in E. coli (LacY) transports both anomeric states of disaccharides but has greater affinity for α-sugars. Molecular dynamics (MD) simulations are used to probe the protein-sugar interactions, binding structures, and global protein motions in response to sugar binding by investigating LacY (the experimental mutant and wild-type) embedded in a fully hydrated lipid bilayer. A total of twelve MD simulations of 20-25ns each with β(α)-D-galactopyranosyl-(1,1)-β-D-galactopyranoside (ββ-(Galp)(2)) and αβ-(Galp)(2) result in binding conformational families that depend on the anomeric state of the sugar. Both sugars strongly interact with Glu-126 and αβ-(Galp)(2) has a greater affinity to this residue. Binding conformations are also seen that involve protein residues not observed in the crystal structure, as well as those involved in the proton translocation (Phe-118, Asn-119, Asn-240, His-322, Glu-325, and Tyr-350). Common to nearly all protein-sugar structures, water acts as a hydrogen bond bridge between the disaccharide and protein. The average binding energy is more attractive for αβ-(Galp)(2) than ββ-(Galp)(2), i.e., −10.7±0.7 and −3.1±1.0 kcal/mol, respectively. Of the twelve helices in LacY, Helix-IV is the least stable with ββ-(Galp)(2) binding resulting in larger distortion than αβ-(Galp)(2).